A promoter toolbox for tissue-specific expression supporting translational research in cassava (Manihot esculenta) - Zierer, Wolfgang; Anjanappa, Ravi Bodampalli; Lamm, Christian Erwin; Chang, Shu-Heng; Gruissem, Wilhelm; Sonnewald, Uwe (Frontiers in Plant Science, 2022)
There is an urgent need to stimulate agricultural output in many tropical and subtropical countries of the world to combat hunger and malnutrition. The starchy crop cassava (Manihot esculenta), growing even under sub-optimal conditions, is a key staple food in these regions, providing millions of people with food. Cassava biotechnology is an important technique benefiting agricultural progress, but successful implementation of many biotechnological concepts depends on the availability of the right spatiotemporal expression tools. Yet, well-characterized cassava promoters are scarce in the public domain. In this study, we investigate the promoter activity and tissue specificity of 24 different promoter elements in stably transformed cassava plants. We show that many of the investigated promoters, especially from other species, have surprisingly low activity and/or tissue specificity, but feature several promoter sequences that can drive tissue-specific expression in either autotrophic-, transport- or storage tissues. We especially highlight pAtCAB1, pMePsbR, and pSlRBCS2 as strong and specific source promoters, pAtSUC2, pMeSWEET1-like, and pMeSUS1 as valuable tools for phloem and phloem parenchyma expression, and pStB33, pMeGPT, pStGBSS1, as well as pStPATATIN CLASS I, as strong and specific promoters for heterotrophic storage tissues. We hope that the provided information and sequences prove valuable to the cassava community by contributing to the successful implementation of biotechnological concepts aimed at the improvement of cassava nutritional value and productivity.